Piece by piece: understanding graffiti-writing in Hong Kong. Issue 1 (3rd May 2016) - Chan, Ho Man; Ku, Ka Chun; Li, Pak Kei Toma; Ng, Hiu Kwan; Ng, Suet Yi Michelle
Abstract : Purpose: This paper aims to examine the development of graffiti in Hong Kong. Based on cultural criminological theories, the study looks at graffiti from the cultural verstehen perspective (Ritzer, 1996) – giving voice to graffiti writers, instead of focusing on how the police or the general public react to the graffiti issue. The research also examines the motives of those writers and whether they perceive graffiti as an act of vandalism or an expression of an art form. Design/methodology/approach: Graffiti is still an underdeveloped research topic in Hong Kong, which is absent not only in the mainstream discourse, but also in mainstream arts. It merely catches the media's attention when graffiti are associated with political struggles. Thus, this paper aims to bridge the gap between the existing literature reviews and the graffiti development in this cosmopolitan city. In particular, it gives voice to graffiti writers to let readers understand how this hidden group of people perceive the notion of graffiti within their own subcultural discourse – and, at the same time, how the public responds to those graffiti-writings. Findings: The research project, to a certain extent, manifests similarities to the literature reviews at an international level, especially the graffiti studies in London and New York. There are similarities in the graffiti styles – tags, bombs and pieces – and also in terms of the meanings carried behind graffiti-writing in public spaces, which showcase power through occupying space and its association with commercialization. Nevertheless, graffiti in Hong Kong have certain unique features, particularly as regards the official response to graffiti and the linkage of graffiti with politics. As seen in the Umbrella Movement and the Ai wei-wei incident, the legal responses were rigid and efficient, showing that the government paid great attention to the messages delivered in these cases. When no complaints or reports are made to the police, graffiti work is left undisturbed. Only when strong political messages are carried will prompt action be taken. Originality/value: Graffiti are an underdeveloped research topic in Hong Kong, which is absent not only in the mainstream discourse but also in the mainstream arts. This paper aims to bridge the gap between the existing literature reviews and the graffiti development in Hong Kong. It gives voice to graffiti writers to let readers understand how this hidden group of people perceives the notion of graffiti within their own subcultural discourse and how city dwellers respond to those graffiti-writings.